Missed diagnosis of imperforate hymen later presenting with hypertension. Issue 9 (9th September 2020) - Chia, Moira; Ho, Christopher
Abstract : An adolescent girl presented with hypertension and was found to have haematocolpos and imperforate hymen. She had a background of chronic abdominal pain and had sought medical attention multiple times prior, with the diagnosis being missed as pubertal evaluation and perineal examination had been neglected during those visits. Hypertension resolved following hymenectomy and drainage of haematocolpos with no long-term sequelae.